Diversity of Medicinal Plants Resources to be Useb by the Kho Mu Community in Special Use Forest, Sop Cop District, Son La Province - Lien, Vu Thi; Dau, Song A; Nghia, Leo Van (VNU Journal of Science: Natural Sciences and Technology, 2021)
This research was conducted to assess the diversity of medicinal plant resources in special use forest, Sop Cop district, Son La province.By traditional botanical research method that we  carried  out since July 2019 to March 2020.The results showed that, there were 389 species of medicinal plants belonging to 294 genera and 109 families of 4 divisions of vascular plant. There were 10 families with the high number of species. The medicinal plants were used differently by the Kho Mu ethnic to treat 18 groups of diseases, of which the plants were used to treat gastrointestinal diseases had the highest percentage of species, 102 species (26,22%). In the parts used as medicine, leaves are most used accounting for from 26,74%. The whole trees and roots were used also quite large, including whole tree with 77 species, roots with 66 species. There were 28 medicinal species (accounting for 7,19%) that had been identified in the Vietnam’s Red Data Book (2007), have 18 species listed in the Vietnam’s Red List of Medicinal Plants,that wrote by Nguyen Tap (2019)  and 12 species listed in the Governmental Decree 06/2019/NĐ-CP. These species had limited individuals that need to have policies for conservation and development.